2001
DOI: 10.1096/fj.01-0457fje
|View full text |Cite
|
Sign up to set email alerts
|

Adipose angiotensinogen is involved in adipose tissue growth and blood pressure regulation

Abstract: White adipose tissue and liver are important angiotensinogen (AGT) production sites. Until now, plasma AGT was considered to be a reflection of hepatic production. Because plasma AGT concentration has been reported to correlate with blood pressure, and to be associated with body mass index, we investigated whether adipose AGT is released locally and into the blood stream. For this purpose, we have generated transgenic mice either in which adipose AGT is overexpressed or in which AGT expression is restricted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
371
2
20

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(420 citation statements)
references
References 36 publications
(12 reference statements)
27
371
2
20
Order By: Relevance
“…[23][24][25] Hall et al 19 reported a more than twofold increase in plasma renin activity after a 5-week period of highfat diet administration in conscious dogs. Moreover, fat restriction succeeded in diminishing the values of the RAS components, indicating the possibility that the degree of adiposity might have a direct influence in this BP-regulating system.…”
Section: Function Of Ras In Obesity Hypertensionmentioning
confidence: 99%
“…[23][24][25] Hall et al 19 reported a more than twofold increase in plasma renin activity after a 5-week period of highfat diet administration in conscious dogs. Moreover, fat restriction succeeded in diminishing the values of the RAS components, indicating the possibility that the degree of adiposity might have a direct influence in this BP-regulating system.…”
Section: Function Of Ras In Obesity Hypertensionmentioning
confidence: 99%
“…Mice with targeted deletion of AGT have decreased blood pressure and adipose tissue mass (68), whereas mice with transgenic overexpression of AGT in adipose tissue have increased blood pressure and adipose tissue mass (69). In addition, mice with transgenic amplification of glucocorticoids due to overexpression 11␤-hydroxysteroid dehydrogenase type 1 (11␤HSD1) in adipose tissue develop hypertension associated with activation of the RAS including increased plasma AGT, angiotensin II, and aldosterone (70).…”
Section: Proteins Of the Renin Angiotensin System (Ras)mentioning
confidence: 99%
“…AGT is extensively produced in adipose tissue, which is responsible for 30 % of its plasma concentration in laboratory rodents (Massiéra et al 2001). In rodent models, angiotensin II contributes to adipose tissue proliferation by binding on both AT1 and AT2 receptors (Kouyama et al 2005;Yvan-Charvet et al 2009), which is opposed by angiotensin 1-7 acting on Mas receptors (Santos et al 2008).…”
Section: Introductionmentioning
confidence: 99%